Influence of etiologic factors on speech perception of cochlear-implanted children. (1st September 2013) - Janeschik, Sandra; Teschendorf, Melanie; Bagus, Heike; Arweiler-Harbeck, Diana
Abstract : Objective Rehabilitation success in cochlear implant patients is influenced by many factors. Influence of different etiologies of deafness on rehabilitation outcome is assessed. Methods Study design Retrospective survey of patients. Setting University hospital. Secondary referral center. Patients One hundred and sixty-three between 1996 and 2008 implanted children (0-18 years, mean 5.17 years). Interventions Evaluation of patients' data: origin of deafness, hearing and speech test results. Access Data Base; Wilcoxon and t- test. Results Mean follow-up: 65.4 months. Etiology of deafness in children found in 104 cases: 69 (51.9%) suffered from hereditary hearing loss. All children showed improvement in their auditory performance, children with connexin-26 mutation performed significantly best, Usher and CHARGE-syndrome children significantly worst. Post-meningitic and post-septic children developed slower but reached same levels later. Discussion Primary cause of deafness, among other factors, has a considerable impact on outcome of rehabilitation. This offers possibilities to influence the outcome by etiology-adjusted therapy modules.